Protein nutrition for peak performance - Hamilton, A.; Carlson, A.; Saunders, M.; Tipton, K. (Peak Performance, 2008)
Because protein is so much more than just an essential nutrient - it`s the largest component in the body after water, typically representing about 15% of body weight. What`s more, most of this protein mass is found in muscle, which explains the importance of protein to athletes.